IFPA meeting 2015 workshop report III: nanomedicine applications and exosome biology, xenobiotics and endocrine disruptors and pregnancy, and lipid. (December 2016) - Albrecht, C.; Caniggia, I.; Clifton, V.; Göhner, C.; Harris, L.; Hemmings, D.; Jawerbaum, A.; Johnstone, E.; Jones, H.; Keelan, J.; Lewis, R.; Mitchell, M.; et al.
Abstract: Workshops are an important part of the IFPA annual meeting, as they allow for discussion of specialized topics. At the IFPA meeting 2015 there were twelve themed workshops, three of which are summarized in this report. These workshops were related to various aspects of placental biology but collectively covered areas of pregnancy pathologies and placental metabolism: 1) nanomedicine applications and exosome biology; 2) xenobiotics and endocrine disruptors and pregnancy; 3) lipid mediators and placental function.